A review of HACCP and the South African abattoir hygiene management system towards integration. (2016) - Govender, Reuben
Integrating management systems is a common practice today. This is done particularly to save costs in the continued management of implemented systems. In South Africa, the hygiene management system (HMS) is regulated for application at abattoirs to manage food safety hazards during processing. Similarities have been noted between the HMS and the hazard analysis critical control point (HACCP) system. Some facilities have certified HACCP and/or ISO 22000 system in place in addition to the HMS. Little research has been done on how whether or not these systems can be integrated. As part of an ongoing empirical study, this paper presents a theoretical framework for the integration of HACCP with the HMS. It also presents central points of integration, i.e., the management of critical control points as well as integration of pre-requisite programs (PRPs).